GSTM3 deficiency impedes DNA mismatch repair to promote gastric tumorigenesis via CAND1/NRF2-KEAP1 signaling. (10th July 2022) - Chen, Tao; Jinlin, Duan; Wang, Fan; Yuan, Zhiqing; Xue, Junyan; Lu, Ting; Huang, Wentao; Liu, Yanfeng; Zhang, Yonglong
Abstract: Gastric cancer (GC) is one of the most severe gastric diseases worldwide. However, the molecular basis that drives tumorigenesis and progression is not completely understood, which hinders the efficacy and development of therapeutic options. Glutathione-S-transferases (GSTs) are a group of phase II detoxification enzymes that maintain redox homeostasis; however, their roles in cancers are not well defined. Here, we revealed that the expression of GST family members is significantly impaired in GC tissues. Glutathione-S-transferase mu 3 (GSTM3), a member of GST family, is dramatically downregulated in cancerous tissues and has been identified as an independent prognostic factor in GC associated with tumor differentiation, inhibiting GC cell proliferation and migration in vitro and in vivo. Mechanistically, GSTM3 is transcriptionally activated by NRF2/KEAP1 signaling. As a feedback loop, GSTM3 binds to Cullin-associated and neddylation-dissociated 1 protein (CAND1), an exchange factor for integrating Kelch-like ECH-associated protein 1 (KEAP1) into Cul3-RING ubiquitin ligases (CRL3), to disrupt nuclear factor-erythroid factor 2-related factor 2 (NRF2)/KEAP1 binding and prevent NRF2 ubiquitination and degradation, leading to its activation. A deficiency in glutathione S-Transferase Mu 3 (GSTM3) reduces DNA mismatch repair (MMR) gene expression and increases mutagenesis via CAND1/NRF2 binding. Importantly, GSTM3/NRF2 and KEAP1 were negatively and positively associated with the genomic signature for microsatellite instability, respectively. Clinically, GSTM3, NRF2, and MutS homolog 6 (MSH6) were positively correlated in the GC specimens. This study uncovered a reciprocal regulation between GSTM3 and NRF2 and established a functional and clinical link between GSTM3-NRF2/KEAP1 and MMR during GC cell proliferation and progression, thus providing potential therapeutic targets for GC. Highlights: Glutathione-S-transferases mu 3 (GSTM3) is identified as an independent prognostic factor in GC associated with aggressive phenotypes. GSTM3 binds to CAND1 o disrupt KEAP1/NRF2 binding and prevent NRF2 ubiquitination and degradation. GSTM3 deficiency reduces DNA mismatch repair (MMR) gene expression and increases mutagenesis via CAND1/NRF2. GSTM3/NRF2 are negatively associated with microsatellite instability genomic signature.